2019
DOI: 10.1002/app.48045
|View full text |Cite
|
Sign up to set email alerts
|

Facile and efficient isocyanate microencapsulation via SDBS/PVP synergetic emulsion

Abstract: A binary emulsion system via combination of sodium dodecylbenzenesulfonate (SDBS) and polyvinyl pyrrolidone (PVP) was employed to prepare microcapsules containing isophorone diisocyanate. The effect of different concentrations of SDBS and PVP on the size and distribution of capsules was investigated. The results showed that uniform and size-controllable capsules were synthesized by synergistic function of SDBS and PVP. Characteristics of capsule were studied by optical microscopy, Fourier transform infrared sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In this approach, mixtures of diisocyanate compounds are used for a dual purpose, namely (i) for the formation of polyurea shell and (ii) as self-healing agents, taking advantage of the difference in reactivity of the selected R-NCOs. Typically, the highly reactive methylene diphenyl diisocyanate (MDI) (or prepolymers of MDI, the so-called PAPI) is used for polyurea shell formation and the less reactive aliphatic isophorone diisocyanate (IPDI) is encapsulated in the core as a releasable potential self-healing agent [ 10 , 11 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this approach, mixtures of diisocyanate compounds are used for a dual purpose, namely (i) for the formation of polyurea shell and (ii) as self-healing agents, taking advantage of the difference in reactivity of the selected R-NCOs. Typically, the highly reactive methylene diphenyl diisocyanate (MDI) (or prepolymers of MDI, the so-called PAPI) is used for polyurea shell formation and the less reactive aliphatic isophorone diisocyanate (IPDI) is encapsulated in the core as a releasable potential self-healing agent [ 10 , 11 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…PAPI) is used for polyurea shell formation and the less reactive aliphatic isophorone diisocyanate (IPDI) is encapsulated in the core as a releasable potential self-healing agent [10,11,22].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported on the encapsulation of isocyanate species with the commonly used interfacial polymerization technique, in polyurethane/polyurea (PU/PUa) shelled MCs, and the solvent evaporation method, in biodegradable shelled MCs [ 5 , 6 , 7 , 8 , 9 ]. Isocyanate microencapsulation is typically reported to be achieved using an oil-in-water (O/W) micro-emulsion system combined with the interfacial polymerization technique [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. It is a simple, reliable, well-studied, and low-cost process to produce isocyanate-loaded MCs.…”
Section: Introductionmentioning
confidence: 99%
“…The microencapsulation of isocyanate dates from 2008, with the encapsulation of monomeric isophorone diisocyanate (IPDI) [ 10 ], resourcing to a 2,4-TDI prepolymer, as a higher reactivity isocyanate, for the shell formation, and 1,4-butanediol as an extra active hydrogen (H) source and chain extender. Other isocyanates used for the shell formation, as well as other active H sources have been reported for the synthesis of IPDI loaded MCs, obtained using the referred technique [ 11 , 12 , 13 , 14 , 15 , 16 ]. Despite their advantages, the obtained MCs are not temperature responsive, have a poor shelf life and their shell exhibits none or low biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…17 19 Yang et al 19 firstly synthesized isophorone diisocyanate (IPDI) microcapsules via interfacial polymerization of toluene diisocyanate prepolymers in oil-in-water emulsion, and numerous isocyanates encapsulation microcapsules have been reported till now. 20 24 Wang et al 25 discussed the preparation of microcapsules filled with IPDI in a sodium dodecyl benzene sulfonate (SDBS) aqueous solution and proved that the mechanical properties of the microcapsule shells could be adjusted by the introduction of oxygen plasma treated carbon nanotubes. Di Credico et al 16 discussed the effects of single layer and bilayer shells on the synthesis of microcapsules containing IPDI in a gum arabic emulsion system and found that double layered capsules showed 50–70 wt% core content, well dispersed, and excellent corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%